Differential Effects of Nitrogen, Phosphorus and Potassium Soil Enrichment on Mycorrhization, Nutritional Status and Nutrient Resorption in Nothofagus Antarctica - Fioroni, Facundo (2025)
Fil: Fioroni, Facundo. Universidad Nacional de Río Negro. CONICET. Instituto de Investigaciones en Recursos Naturales, Agroecología y Desarrollo Rural. Río Negro, Argentina.